Preventive effects of probiotics on dental caries in vitro and in vivo - Jingyan Zhang; Qian Wang; Zhi Duan (BMC, 2024)
Abstract Background Dental caries is a common disease in the oral cavity, and the microorganisms in the cavity are colonized in the form of dental plaque biofilm. Streptococcus mutans is the main pathogen causing dental caries. Using probiotics to inhibit the growth and colonization of pathogenic bacteria, regulate mucosal immunity and improve oral microecological balance is an effective way to prevent or treat dental caries. The aim of this study was to evaluate the caries-prevention of probiotics in vitro and in rat caries models. Methods The probiotics used in this study are a combination of 4 strains of bacteria. After the fermentation of 4 strains (L. plantarum, L. salivarius, L. rhamnosus, and L. paracasei) was completed, they were mixed in equal volume proportions and used as samples to be tested. The mixture was then assessed the ability to inhibit the growth of S. mutans in vitro and in vivo. SPSS Statistics 22.0 (SPSS, Inc., Chicago, IL, USA) was used for analysis. Results In vitro the probiotics mixture could inhibit the growth of S. mutans and was able to remove biofilms formed by S. mutans. In a 42-day in vivo experiment, the probiotics group significantly reduced the level of S. mutans on the tooth surface of rats, reducing more than half the bacterial quantities compared with the caries model group (P < 0.05). The amount of S. mutans in the antagonist group was low and highly significant compared with the caries model group. Moreover, the mixture of 4 strains significantly reduced the caries scores (modified Keyes scoring method) in both the probiotic and antagonist groups (p < 0.05). Conclusions The study showed that the combination of the four strains can reduce the cavity scores, and the four strains can be used as products in oral care products. At the same time, the study also suggests that probiotic therapy can be an effective way to prevent dental caries.